Assessment of anthropometric and body composition characteristics of elite Turkish wrestlers - Yaşar Berkay; Sağır Mehmet (Sciendo, 2021)
Study aim: The aim of the study was to determine the anthropometric characteristics of elite Turkish wrestlers according to their weight categories.